The Accumulation of NaCl in The Coastal Plant Leaves of Mangrove, Bariongtonia, and Pes-Caprae Formations - Rusdi Hasan; Tia Setiawati; Marheny Lukitasari; Nopriyeni Nopriyeni (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to compare the salt content (NaCl) in the leaves of several types of coastal plants that grow in different formations, namely Mangrove, Barringtonia, and Pres-Caprae. The study was conducted in the coastal area of Lais District, North Bengkulu Regency using direct survey methods in the field and laboratory analysis using a refractometer. The results showed that there were 10 species of coastal plants from three formations, namely Barringtonia, Mangrove, and Pes-Caprae. The highest salt content was found in the Acanthus species ilicifolius (2.75) from the Mangrove formation, while the lowest levels were found in Canavalia maritima (0.75) from the Pes-Caprae formation. The difference in salt content is thought to be influenced by the location of its habitat in the coastal area and its ability to adapt both structurally and physiologically so that it can survive in an environment with extreme salt content. The results of this study provide important information about the adaptation of coastal plants to salinity and can be the basis for further research on salt concentration in coastal plants.